2020
DOI: 10.3390/ijms21186542
|View full text |Cite
|
Sign up to set email alerts
|

The Bladder EpiCheck Test as a Non-Invasive Tool Based on the Identification of DNA Methylation in Bladder Cancer Cells in the Urine: A Review of Published Evidence

Abstract: Recently, there has been a great effort to develop tests based on non-invasive urinary biomarkers (NMIBCs). These tests are based on the fact that NMIBCs are heterogeneous at the molecular level and can be divided into different molecular groups useful to predict prognosis and response to treatment. The assessment of epigenetic alterations, such as DNA methylation, represents a promising cancer biomarker. DNA methylation is an epigenetic modification that affects gene expression without modifying the DNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 20 publications
(55 reference statements)
0
35
0
Order By: Relevance
“…The dual-marker assay (sensitivities of 88.1–91.2% and specificities of 85.7–89.7%) also exhibited comparable performance to the methylation assay currently in the Europe’s study, the Bladder EpiCheck, with reported sensitivities of 62.5–90% and specificities of 82.1–90.0% [ 28 ]. While the Bladder EpiCheck utilizes a panel of 15 methylation markers, the assay of dual-marker and five-marker three-class risk stratification models can further reduce the cost in a clinical screening setting.…”
Section: Discussionmentioning
confidence: 99%
“…The dual-marker assay (sensitivities of 88.1–91.2% and specificities of 85.7–89.7%) also exhibited comparable performance to the methylation assay currently in the Europe’s study, the Bladder EpiCheck, with reported sensitivities of 62.5–90% and specificities of 82.1–90.0% [ 28 ]. While the Bladder EpiCheck utilizes a panel of 15 methylation markers, the assay of dual-marker and five-marker three-class risk stratification models can further reduce the cost in a clinical screening setting.…”
Section: Discussionmentioning
confidence: 99%
“…The Bladder EpiCheck (Nucleix; Rehovot, Israel) test is based on an analysis of the panel of 15 DNA (deoxyribonucleic acid) biomarkers, associated with urinary bladder carcinoma. The test requires small amounts of DNA, isolated from easily available urine samples, while being simultaneously characterised by very high, clinically proven sensitivity, specificity and negative predictive value [ 5 ]. The Bladder EpiCheck test has been designed for the non-invasive monitoring of malignant relapses.…”
Section: Methodsmentioning
confidence: 99%
“…DNA methylation pattern changed during progression from NMIBC to MIBC [ 27 ]. Changes in DNA methylation pattern of a panel of 15 genomic biomarkers detected by RT-PCR was used in the Bladder EpiCheck (Nucleix, Rehovot, Israel) [ 28 ]. The test provides a score, which is considered positive for values higher than 60 [ 29 ].…”
Section: Dna Methylationmentioning
confidence: 99%